Comparative Study of Laboratory Based Chlorophyll - A Determination Methods - Grósz, János; Sebők, András; Waltner, István (Journal of Central European Green Innovation, 2022)
Protecting the quality and quantity of the available surface water resources is one of the most important points. Water quality is a complex concept that includes the physical, chemical, biological and hydrological parameters of water. One of the most significant biological water quality parameters is the chlorophyll-a content. Several different laboratory and field measurement methods are used to determine the chlorophyll-a content of water samples. The most frequently used laboratory methods are the Felföldy 1987 and the ISO 10260:1992 methods. Among field determination methods, submersible probes are frequently used to measure the chlorophyll-a concentration. Previously mentioned methods are based on fluorescence techniques. The main aim of this recent study is to compare different laboratory chlorophyll-a determination methods. Among the applied approaches, the Felföldy 1987 method and the ISO 10260:1992 method were compared. Furthermore, we measured the effect of the different solvent on the determination methods. Based on this, we investigated the Felföldy determination method using different solvents (methanol substituted with ethanol). The measurements were carried out under the same conditions from samples of Chlorella vulgaris culture in three repetitions by preparing a dilution series.